E-Modul Interaktif untuk Memfasilitasi Pemahaman Konsep Peserta Didik - Azin Taufik Taufik; Anggar Titis Prayitno; Nunu Nurhayati; Nirma Sintia (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2024)
The aim of this research is to develop interactive E-Module based teaching materials that are valid and easy to use to improve students' understanding of mathematical concepts. This research is included in the development research category which follows the Plomp model which consists of four steps, namely (1) preliminary research; (2) prototype stage (prototyping stage); (3) assessment stage and (4) systematic documentation stage. The instruments used in this research include validity test questionnaires, practicality test questionnaires, and tests. Product validity was evaluated by material experts with results reaching 82.3% (very valid), design experts gave an assessment of 94.2% (very valid), and language experts gave an assessment of 77.5% (valid). The practicality of this product is well proven, as was found in the practicality test, teacher responses reached 95% (very good), and the overall student response practicality test reached 90.6% (very good). Interactive e-modules have proven successful in facilitating understanding of mathematical concepts, demonstrated by a high level of concept understanding of 90%. Thus, it can be concluded that the interactive E-Module based teaching materials developed are valid and practical in helping students understand mathematical concepts